2009
DOI: 10.1002/ijc.24705
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous expression of the sodium iodide symporter mediates uptake of iodide in murine models of colorectal carcinoma

Abstract: The sodium iodide symporter (NIS) mediates iodide uptake into the thyroid. Because of this mechanism, differentiated thyroid cancer is susceptible for radioiodine therapy. Functional NIS expression in extrathyroidal tumors has been reported mainly in breast cancer. We screened colorectal tumors for NIS expression and investigated the mechanisms regulating NIS activity. Cell lines were screened for iodide uptake in vitro and NIS expression was evaluated by real-time RT-PCR, immunocytochemistry and immunoblottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Active uptake of pertechnetate has been noted before in other tumours [27,28], where it has been shown to be due to endogenous iodide symporter (NIS) expression, but in the case of VX2 liver tumours we found that while a competitive inhibitor of the NIS (perchlorate)…”
Section: Discussionsupporting
confidence: 61%
“…Active uptake of pertechnetate has been noted before in other tumours [27,28], where it has been shown to be due to endogenous iodide symporter (NIS) expression, but in the case of VX2 liver tumours we found that while a competitive inhibitor of the NIS (perchlorate)…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, studies regarding the hormones in close proximity to the thyroid, which may be involved in the sychronous primary tumor mechanism, such as thyroid hormone ( 9 ), thyroid peroxidase antibody ( 10 ) and thyroid Ras-regulating enzymes ( 11 ), have been undertaken. The sodium iodide symporter (NIS) was proposed as a potential co-passageway for thyroid and BC ( 12 , 13 ), indicating a potential therapeutic target during radioiodine therapy. Therefore, the specific signaling pathways regulating NIS activity require investigation and a method to upregulate NIS must be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its specificity and sensitivity, qRT-PCR is the method of choice for quantifying mRNA expression levels of cytokines, which normally are expressed at very low levels (Giulietti et al, 2001). Most qRT-PCR protocols have been developed to quantify cytokines in mice and humans, owing to the availability of a complete collection of leukocyte expressed sequences tags (ESTs) and complete genomic sequences for those species (Bilate et al, 2008; Castilho et al, 2008; Dantas et al, 2009; Fang et al, 2009; Gaertner et al, 2009; Suksumek et al, 2008; Walsh et al, 2009). In contrast, very few assays have been developed for quantification of cytokines in domestic animals (Ledger et al, 2004; Leutenegger et al, 1999a,b).…”
Section: Introductionmentioning
confidence: 99%